A 5 m/25 Gbps Underwater Wireless Optical Communication System - Chung-Yi Li; Hai-Han Lu; Wen-Shing Tsai; Zhen-Han Wang; Chung-Wei Hung; Chung-Wei Su; Yi-Feng Lu (IEEE Photonics Journal)
A 25-Gbps underwater wireless optical communication (UWOC) system with a two-stage injection-locked 680-nm red-light vertical-cavity surface-emitting laser (VCSEL) transmitter to enhance the frequency response and a laser beam expander to expand the collimated beam diameter over a 5-m highly turbid harbor water link is proposed and practically demonstrated. In highly turbid harbor water link, the overall attenuation coefficient at 680 nm is smaller than that at 520 and 450 nm, thereby a 680-nm red-light VCSEL transmitter is adopted in this proposed 5 m/25 Gbps UWOC system rather than a 520-nm green-light laser diode (LD) transmitter or a 450-nm blue-light LD transmitter. A satisfactory bit error rate performance (3 × 10–9) and a clear eye diagram are acquired in real time. This proposed UWOC system with a two-stage injection-locked 680-nm VCSEL transmitter and a laser beam expander brings important improvements in the scenario characterized by high turbidity.